THE RELATIONSHIP BETWEEN PREECLAMPSIA AND LOW BIRTH WEIGHT (LBW) IN WONOSARI, GUNUNGKIDUL REGIONAL HOSPITAL - Dwi Wahyuni; Elika Puspitasari (Universitas Ahmad Dahlan, 2021)
Background: Globally, the infant and maternal mortality rate is still a severe problem because it was an indicator of national health – no exceptions for Indonesia. In 2017, the average infant mortality rate was 76 per 1,000 live births, while in Yogyakarta, it was 313 cases. The most common causes of infant and neonatal mortality were low birth weight babies (LBW) and sepsis. In 2018 in Wonosari, Gunungkidul Regional Hospital found 1,421 new-borns were normal, and 298 infants were experiencing LBW. This study aims to determine preeclampsia's relationship with the incidence of low-birth-weight babies (LBW) in Wonosari, Gunungkidul Regional Hospital Year 2018. Method: This research was conducted in Wonosari, Gunungkidul Regional Hospital, using quantitative analysis with a case-control approach. The case population was 280 and using the Slovin formula. We recruited 170 controls and 170 cases. Inclusion criteria used include (1) Babies born with low birth weight <2,500 grams; (2) a single fetus; and (3) recorded in the medical record at the hospital. Results: There was a significant relationship between preeclampsia with low-birth-weight babies (LBW) in Wonosari, Gunungkidul Regional Hospital 2018 with a p-value of 0.004 (p <0.05) and crude OR 2.114; 95% CI (1.268-3.523). Conclusion: Pregnant women with preeclampsia will be at greater risk of giving birth to a baby with LBW.